The way home - Lee, Jung- Hyang (Singapore, 2003)
This is the story of 7- year old, "Sang Woo", born and raised in the big city, and his mute grandmother, who spent her whole life in a small rural village. Forced to stay with his grandmother, Sang-Woo learns about the ups and downs of life. Being a city boy, used to the benefits and luxuries of the modern world, he comes into conflict with a person whose soul is close to nature. Mother, like his grandmother, is silent and patient. She never argues and she gives in to other's demands. Nevertheless, she has an inner strength and a shoulder to cry on in time of need. The grandma of nature may wield to the whims of her grandson, representing the material world, but the moves him in the end. The film creates the emotional freedom for to reminisce over the wisdom of life and our most cherished resource- nature